Cardiac diagnostics before oral propranolol therapy in infantile hemangioma: retrospective evaluation of 234 infants - Frongia, Giovanni; Arnold, Raoul; Mehrabi, Arianeb; Günther, Patrick (World journal of pediatrics, 2018)
BackgroundThe indication and extent of cardiac screening before oral propranolol therapy (OPT) in patients with infantile hemangioma (IH) has been challenged. In this study, we evaluated pre-OPT cardiac diagnostics in a pediatric IH cohort in our department.MethodsRetrospective chart review of infants ≤ 12 months old with IH undergoing OPT. The diagnostics prior to OPT, occurrence of complications, and outcome were recorded.ResultsA total of 234 patients were evaluated. The mean age at the onset of OPT was 4.2 ± 0.3 months, the average duration of OPT was 6.1 ± 0.1 months, and the average follow-up was 12.3 ± 0.7 months. Echocardiograms and electrocardiograms were performed prior to OPT in all patients. One hundred and three (44.0%) echocardiograms revealed pathological findings, 19 (8.1%) of which were minor (including atrial septal defects, pulmonary stenosis, and patent ductus arteriosus). Pathological findings were observed in 17 (7.3%) of electrocardiograms, only one (0.4%) of which was minor (suspected cardiac arrhythmia, subsequently excluded by long-term electrocardiogram analysis). These findings did not contraindicate OPT and no severe adverse events associated with OPT occurred during the follow-up period.ConclusionsRoutine cardiac screening by electrocardiogram and echocardiogram before OPT is debatable and not routinely indicated in children with IH. Further studies are necessary to draw definite conclusions on the reasonable indication and extent of this diagnostic approach.
Gesehen am 08.08.2019